PENGEMBANGAN MEDIA BUDISI (BUKU AUDIO PUISI) PADA MATERI PUISI KELAS IV UPT SDN 137 GRESIK - Sahid Risky Setiawan (JUSEDA, 2022)
This study aims to develop BUDISI media on poetry material for grade IV Elementary School UPT SDN 137 Gresik and determine the validity of BUDISI media and determine students' writing skills after using BUDISI media in learning. This research was conducted at UPT SDN 137 Gresik using a research model developed by Robert M. Branch, namely the ADDIE model: Analysis (analisis), Design (Perancangan), Development (Pengembangan), Implementation (Implementasi), and Evaluation (Evaluasi). This study uses data validity analysis, student response analysis, and student writing ability analysis. On the validity of the data, the aspects assessed are the Graphical aspect, the Linguistic aspect, the Material Aspect and the Presentation Aspect. The results given by the validator to the BUDISI media obtained an average proportion of 92.16% and included in the "very valid" criteria. The test results for student responses and the ability to write poetry respectively obtained a percentage of 91.3% and 83.3% included in the "very good" criteria so that the BUDISI media was suitable for use in the Indonesian language learning process in poetry material